2002ネン オヨビ 2003ネン カキ ナンキョクカイ ノ トウケイ 140ド セン ニ ソッタ プランクトン ノ ブンプ パターン - 谷村, 篤; タニムラ, アツシ; 岡, 信和; オカ, ノブカズ; 川口, 創; カワグチ, ソウ; 西川, 淳; ニシカワ, ジュン; 高橋, 邦夫; タカハシ, クニオ; 真壁, 竜介; マカベ, リュウスケ; et al. (情報・システム研究機構 国立極地研究所, 2008)
P(論文) 2002年及び2003年の南極海の夏季,東部インド洋区のウイルクスランド沖の東経140度線上において,白鳳丸及びタンガロアによる3回の調査航海によって行われたRMT-8(目合: 4.5mm, 開口面積: 8m3)ネット採集によって得られた標本に基づいて,大型動物プランクトン群集構造を調べた.クラスター解析の結果,大型動物プランクトン群集は,南極周極流の南縁(SB-ACC: Southern Boundary of the Antarctic Circumpolar Current)で大きく二つの群集に分けられた.すなわち,SB-ACCの北方では大型動物プランクトン群集は,Salpa thompsoni, Euphausia frigida及びThemisto gaudichaudiiなどのoceanic communityが卓越していた.一方,SB-ACCの南方ではEuphausia superba及びEuphausia crystallorophiasなど大陸寄りに主分布域をもつ動物プランクトンが卓越していた.SB-ACCは,南極海の上記の主要な大型動物プランクトン種の出現の差によって特徴付けられることが示唆された. Field surveys were conducted along 140°E in the Southern Ocean north of Terre Adelie during three cruises: the KH cruise by RV Hakuho Maru, and TC1 and TC2 cruises by RV Tangaroa during the austral summers of 2002 and 2003. Macrozooplankton were sampled using a Rectangular Midwater Trawl (RMT 8: mesh size: 4.5mm; effective mouth area: 8m2) along each transect. Macrozooplankton communities were separated by the Southern Boundary of the Antarctic Circumpolar Current (SB-ACC) based on cluster analysis. North of the SB-ACC, macrozooplankton assemblages comprised species of the northern oceanic community characterized by Salpa thompsoni, Euphausia frigida and Themisto gaudichaudii, while south of the SB-ACC, macrozooplankton assemblages were numerically dominated by Euphausia superba and/or Euphausia crystallorophias. It is suggested that the SB-ACC functions as the major biogeographic barrier to separate the macrozooplankton communities, and the contributions of macro- and meso-zooplankton to total zooplankton abundance varies seasonally as well as regionally in the Indian sector of the Southern Ocean crossing the SB-ACC. departmental bulletin paper